Types of Articulation Errors Produced by 3,5 Years Old Child: Study Case of PA - Nurjanah, Anisa; Indriyani, Vivi (Universitas Cokroaminoto Palopo, 2024)
Articulation errors are often found in children. One of them is PA, 3.5 years old, a preschool student. This study aims to describe articulation errors shown by PA when communicating. This error will have a negative effect on PA if left without proper treatment. The author collected data by recording every word pronounced by PA according to the author's request. Then, the author pays attention to the articulation errors made and groups these errors into four types of articulation errors proposed by Fogle (2017). The author found three types of articulation errors that were often made by PA. PA shows a substitution error in the sound /s/ which changes to the sound /t/ if it is located at the end of the word. However, it changes to /c/ if it is located at the beginning and middle of a word. The sounds /r/ and /l/ change to /n/ when they are at the end of a word, but /r/ changes to /l/ when they are at the beginning and middle of a word. The /n/ sound will change to /ꬼ/ if it is in the middle of a word that has repeated sounds. The author also found omission errors, namely the sounds /g/, /k/, /d/, /j/ will be lost if they are at the beginning of the word. The sounds /l/ and /r/ will also disappear if they are in the middle of a word. Errors in adding sounds were found in the middle of words in the form of a nasal /m/ sound if followed by a /b/ sound and an /n/ sound if followed by a /d/ sound. Meanwhile, the sounds /n/ and /ꬼ/ will appear in the middle of words that have repeated sounds.